The leader a new face for American management - Maccoby, Michael (New York Simon and Schuster, 1981)
The Leader,? an entirely new breed of manager, has seized the reins of power, looking beyond money and status alone toward inspiring a team that fulfills company and personal expectations.
Includes bibliographical references and index.
Keywords: Leadership